The Effectiveness of YouTube Media to Improve Knowledge and Literacy of Elementary School Students - Muhammad Alvan Mulya; Rina Maryanti; Verra Wulandary; Asep Rudi Irawan (Universitas Pendidikan Indonesia (UPI), 2023)
Indonesia's low literacy rate makes Indonesia lagging behind several other countries. The purpose of this study is to improve technological literacy in school students. This study uses the YouTube application as a medium to improve technological literacy. The method used is descriptive quantitative with an approach using a pre-experimental method in the form of a one-group pre-test post-test design. The results of this study an increase in knowledge of technological literacy by 42%. The pre-test result of 28% increased to 70% after being given treatment. YouTube media is proven to be able to improve technological literacy in elementary school students and can be used as a technology literacy media.